Scandium alkyl and hydride complexes supported by a pentadentate diborate ligand: reactions with CO2 and N2O. Issue 38 (13th September 2018) - Beh, Daniel W.; Piers, Warren E.; del Rosal, Iker; Maron, Laurent; Gelfand, Benjamin S.; Gendy, Chris; Lin, Jian-Bin
Abstract : Alkyl and hydrido scandium complexes of the dianionic pentadentate ligandB2 Pz4 Py are reported. Abstract : Alkyl and hydrido scandium complexes of the dianionic pentadentate ligandB2 Pz4 Py are reported. The key starting material (B2 Pz4 Py)ScCl is readily prepared and alkylated with organolithium reagents RLi (R = CH3, CH2 SiMe3, CH2 SiMe2 Ph, CH2 CH2 CH3 and CH2 CHMe2 ) to form alkyl derivatives in 61–93% yields. These compounds are very thermally stable and do not undergo sigma bond metathesis reactions with dihydrogen. The hydrido complex was prepared from (B2 Pz4 Py)ScCl and NaHBEt3 in 80% yield and was found to be more stable by 28 kcal mol −1 as a dimer, rather than a monomeric hydrido complex. However, the monomer is accessible through dissociation of the dimer at 80 °C. All of the compounds (B2 Pz4 Py)ScR react with water to form the bridging oxo dimer (B2 Pz4 Py)ScOSc(B2 Pz4 Py). The reactivity of the hydrido and methyl complexes towards carbon dioxide was explored; heating to 80 °C results in the formation of κ 2 formato and acetate complexes, respectively. The mechanisms were studied via density functional theory and distinct transition states for insertion of CO2 into the Sc–R (R = H, CH3 ) were found, with the insertion into Sc–CH3 being more enthalpically difficult (by 18 kcal mol −1 ) than insertion into Sc–H. The slow rate of reaction between [(B2 Pz4 Py)ScH]2 and CO2 is attributed to the barrier associated with dimer dissociation. In both insertion reactions, the kinetic products are κ 1 formato or acetate complexes that are only slightly less stable than the observed κ 2 derivatives. The κ 1 compounds can therefore be trapped by treating the κ 2 isomers with tris-pentafluorophenyl borane.